2025 Cattlemen's Day Full Report (Kansas Agricultural Experiment Station Research Reports, 2025)
This report includes research conducted in 2024 on beef cattle management, nutrition, and meat science conducted at Kansas State University. Specific topics include effects of prescribed burning and grazing in the Flint Hills, feeding techniques and methods in feedlots, nutrition supplements for improved health management, and beef thawing methods and consumer preferences.
Keywords: beef cattle management; nutrition; meat science; prescribed burning; feedlots; consumer preference